Simulação da alimentação volumosa em sistemas de produção de leite no semiárido brasileiro - Silva, Gutenberg Lira (2013)
The objective of this study was characterization and application of a simulation model for the bioeconômica evaluation of feeding strategies in milk production systems in semiarid conditions with emphasis on the type of bulk food used. The study occurred in the region of Baixo Jaguaribe, in state of Ceará, with monthly data obtained on 45 producers and grouped into zootechnical and economic indicators. The CNCPS v.5.0 and Microsoft Excell® programs were used, to simulate the demands of nutrients for cows of different milk yield levels. Multiple regressions and Linear Programming model (LP) were used for analysis of tracks (minimum, maximum, medium, R$ 500 and R$ 1,000) for RMCA of milk activity, of rearing heifers, and of pasture area available for heifers, respectively. Beyond, the minimum, maximum, medium, 40% and 60% of the daily cost of milk production (DCM). The daily milk yield was higher in the Mixed Dryland (MD) and Rotational Stocking (RS) systems (84.21 and 77.36 L∙dia-1), respectively. The LR showed higher productivity per area (13,547 L∙ha-1∙ano-1, in areas of 2.63 ha). The rate of pay invested capital (RPIC) was 1.42% for Irrigated Grass. Higher milk production in lactation (MPL) reduces the DCM, inversely to the effect the variable body weight (BW) and fat content of milk (FCM). The DCM, for 100 L daily, on average, varied between R$ 25.43 in CAA3+TANZ1 system to R$ 62.50 in CAA1+SILMIL3 system. Higher average RMCA (R$ 3.524,29 ha-1∙mês-1) was obtained in CAA3+TANZ1 system. The LP showed that the MPL is more determinant in adjustment of the RMCA, using cows with lower BW and lower FCM. The maximum RMCA in rearing heifers was R$ 8,846.81 ha-1∙ano-1, in TANZ+TANZ system. The simulation makes it possible to identify variables related to the animal and forages can influence the RMCA.